Telehealth is Crucial for Pain Medicine: Patients and Doctors are at the Brink, and Medicare Must Act Now - Pritzlaff SG; Singh N; Sanghvi C; Schatman ME (Journal of Pain Research)
Scott G Pritzlaff,1 Naileshni Singh,1 Chinar Sanghvi,1 Michael E Schatman2,3 1Department of Anesthesiology and Pain Medicine, University of California, Davis, Sacramento, CA, USA; 2Department of Anesthesiology, Perioperative Care and Pain Medicine, NYU Grossman School of Medicine, New York, NY, USA; 3Department of Population Health - Division of Medical Ethics, NYU Grossman School of Medicine, New York, NY, USACorrespondence: Michael E Schatman, Department of Anesthesiology, Perioperative Care & Pain Medicine, NYU Grossman School of Medicine, 550 First Avenue, New York, NY, 10016, USA, Tel +1425-647-4880, Email Michael.Schatman@NYULangone.org